Stan Graniczny Rurociągu Cienkościennego w Przypadku Ciśnienia Wewnętrznego i Zginania - Mrowiec, M. (Engineering Transactions, 1966)
The subject of this analysis is the limit state of a thin-walled rectilinear pipeline made of a perfect elastic-plastic material and loaded in a static manner by an internal pressure and a bending moment acting simultaneously. Circumferential bending of the wall is taken additionally into consideration. The problem is reduced to the determination of the limit curve (4.9) in dimensionless quantities m = f(q, t, ϕ0)  by means of the statistical method. In addition, the stress distributions σz and σθ in the pipeline are given as an example, in two cases of load of the pipeline the influence of bending being shown to be small as compared with that of the internal pressure.The linear ξ = f(θ) separating the zone of circumferential tension from the zone of circumferential compression in the cross-section of the pipeline is also determined [Eq. (4.6)].